Fluorine-18: An untapped resource in inorganic chemistry - Varlow, Cassis (Chem Commun (Camb), 2018)
Advances in the field of fluorine chemistry have been applied extensively to the syntheses of (18)F-labelled organic compounds and radiopharmaceuticals. However, (18)F has sparely been used as a tool to explore inorganic chemistry and can be viewed as a research area worthy of further development. This review highlights the application of (18)F in development of inorganic fluorinating agents, mechanistic studies and imaging tools.